Bibliometric Analysis of Gamification in Education: Trends, Collaboration, and Future Directions - Wahyudi Mutalib; Benny Prasetiya; Febry Suprapto; Khoiriyah (Immortalis Journal of Interdisciplinary Studies, 2026)
In the past decade, gamification has emerged as an innovative approach in education aimed at enhancing student motivation, engagement, and learning outcomes. By integrating game elements like points, badges, leaderboards, and levels into learning activities, gamification creates a more interactive and engaging learning experience. This study explores the bibliometric analysis of research on gamification in education, with a particular focus on trends, collaboration networks, and future directions. The objective is to identify significant research patterns, major contributors, and the evolution of themes in gamification studies. The research method employs a bibliometric approach, using Scopus and Web of Science databases to gather data from publications between 2022 and 2025. Results indicate a substantial increase in publications on gamification, especially in higher education, medical training, and digital learning technologies. The analysis shows that countries like the United States, Spain, and the United Kingdom lead international collaborations, with journals like BMC Medical Education and PLOS ONE playing a significant role. A key novelty of this study is the integration of bibliometric analysis and network visualization to map the relationships between research topics and authors. This paper contributes to the literature by offering a comprehensive map of gamification research, addressing gaps in the current studies and providing insights into future interdisciplinary research directions, including AI, VR, and social-emotional learning in educational gamification.